2018
DOI: 10.1002/anie.201808098
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrahigh Mobility in Isomorphic Fluorobenzo[c][1,2,5]thiadiazole‐Based Polymers

Abstract: To understand the effects rendered on the relevant basic physical properties and device function by controlling the regiochemistry of the cyclopenta[1,2-b:5,4-b']dithiophene-fluorobenzo[c][1,2,5]thiadiazole polymer (hereafter referred to as the CDT-FBT polymer), two polymers, the regiorandom polymer (RA) and regioregular version (RR), respectively, are synthesized and characterized. In addition, an efficient route for synthesizing a key monomer for RR using various synthesis scope and optimizing the reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 40 publications
1
38
1
Order By: Relevance
“…which shows that high mobility semiconductors should give the highest photoresponsivity as pointed out by Liguori et al [22]. (In this context, the photoresponse of OTFTs based on the recently reported thiadiazole-based polymers (mobility ~17 cm 2 /Vs) [37] would be worth investigating). In the present case, Figures 1 and 2 show that  becomes almost constant at ~1 cm 2 /Vs for 50 V < |VG| < 60 V. Since photoresponsivity also saturates at RMAX in this voltage range, we see from equation (6) that this must be a consequence of the saturation in VT.…”
Section: Discussionmentioning
confidence: 85%
“…which shows that high mobility semiconductors should give the highest photoresponsivity as pointed out by Liguori et al [22]. (In this context, the photoresponse of OTFTs based on the recently reported thiadiazole-based polymers (mobility ~17 cm 2 /Vs) [37] would be worth investigating). In the present case, Figures 1 and 2 show that  becomes almost constant at ~1 cm 2 /Vs for 50 V < |VG| < 60 V. Since photoresponsivity also saturates at RMAX in this voltage range, we see from equation (6) that this must be a consequence of the saturation in VT.…”
Section: Discussionmentioning
confidence: 85%
“…1d). In addition, it has reported that PCDTFBT shows a high mobility of 1.45 and 17.82 cm 2 V À1 s À1 in the spincoated and orientated films [31], which is about 3-4 orders higher than the mobility of Cs 2 AgBiBr 6 films and thus it is high enough to extract the charge carriers. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Titanium tetrachloride (TiCl 4 ), ethanol and diethyl ether were purchased from Sinopharm Chemical Reagent Corporation Co., Ltd. Dimethylsulfoxide (DMSO, 99.9%) was purchased from Sigma-Aldrich. Spiro-OMeTAD (!99.0%) was purchased from Shenzhen Feiming Science and Technology Co. [31]. The purity of gold wire is 99.99%.…”
Section: Methodsmentioning
confidence: 99%
“…7,[9][10][11][12] In most of the high-performance OFETs reported so far, the conventional inorganic materials such as silicon dioxide (SiO2), aluminum oxide (Al2O3) and so on are used as gate dielectrics along with solution-processed OSCs. [13][14][15][16][17][18][19][20] Though, allsolution-processed OFETs are essential for the realization of low-cost, flexible electronic devices, the development of such OFETs in which both the gate dielectric and the semiconductor are organic materials is difficult to achieve. The reason being the difficulty in forming pin-hole free dielectric thin-films with controlled morphology and selection of suitable orthogonal solvent for both the semiconductor and the gate dielectric.…”
Section: Introductionmentioning
confidence: 99%
“…OFETs fabricated with solution-processed OSCs are reported to show field effect mobilities above 10 cm 2 V -1 s -1 . 2,[13][14][15][16][17][18][19][20]39 Crystallinity and uniformity of the semiconducting films critically affect the mobility. In most of the solution-processed films, poor uniformity and high roughness occur due to recrystallization of the materials during solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%